Pesticide upsurge, cross-contamination and biodiversity: case studies from the Caribbean Coast Human-Environment Observatory - Hervé, Vincent; Sabatier, Pierre; Lambourdière, Josie; Raymond, Richard; Foulquier, Eric; Le Berre, Iwan; Lopez, Pascal Jean (Comptes Rendus. Géoscience)
Similar to many small islands within the Wider Caribbean Region, the French West Indies are rich but fragile island ecosystems threatened by global warming, pollutants and other anthropic pressures. To understand integrated and complex human impacts on the environment, the Caribbean Coast Human-Environment Observatory (OHM) is developing disciplinary and interdisciplinary studies related to the local-scale driving factors that affect the coastal evolution in Guadeloupe. We present here results that show the multiple causalities, causal asymmetries, and equifinality of environmental pollution related to chlordecone, glyphosate, arsenic and Sargassum and highlight the need to bring further knowledge and awareness to the local populations on these concerns.